Hazmat Dress Model Development for Health Service - Munjiati, Munjiati; Haryati, Welas; Ratifah, Ratifah; Wahyuningsih, Dyah; Indriyani, Nastiti Nur (Poltekkes Kemenkes Jakarta III, 2022)
Hazmat is one of the Personal Protective Equipment (PPE) used by health workers in dealing with infectious diseases such as tuberculosis, hepatitis, COVID-19 which is currently a pandemic. There are several things that must be considered in the production of this hazmat clothing, namely the type of hazmat material, standardization and comfort in its use. The addition of the outer layer of hazmat clothing using betel leaf extract in the form of spray and liquid which has anti-bacterial and anti-virus activity is expected to increase the safety of health workers to be more protected from bacteria/viruses. This study applies research and development methods (Research and development). The research stages were carried out in the laboratory experimentally by applying betel leaf extract with spray and liquid preparations. The spray preparation that has been prepared is applied to the hazmat shirt by spraying it. After the hazmat is used by health workers in health services, the number of bacteria will be tested in the laboratory